Variasi Konsentrasi Kombinasi Ekstrak Buah Belimbing Wuluh (Averrhoa bilimbi L.) dan Daun Sirih (Piper betle) Menggunakan Metode Hidroekstraksi Seabagai Antibakteri Seara In Vitro - Tilarso, Dara Pranidya; Muadifah, Afidatul; Khusna, Mursyidah Lathifatul (Jurnal Farmasi & Sains Indonesia, 2024)
Infectious diseases caused by bacteria are diseases that often arise in society. Bacteria that cause infection include Staphylococcus aureus and Escherichia coli. Bacterial growth can be inhibited with antibiotics. However, some microbes have become resistant to antibiotics so that the use of antibacterials from natural ingredients has begun to be used. Star fruit (Averrhoa bilimbi L.) contains flavonoids, tannins, saponins which are useful as antibacterials. Betel leaf (Piper betle) contains saponins, tannins, flavonoids and phenolic compounds which have activity in inhibiting bacteria. The purpose of this study was to determine the antibacterial activity of a combination of star fruit and betel leaf extracts. The method used in this study was the hydroextraction method with various concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%. Antibacterial activity testing using disc diffusion. The results showed that the combination of star fruit and betel leaf extracts had optimum inhibitory activity at a concentration of 100% with an inhibition diameter of 11.05 mm for Staphylococcus aureus which was strong and with a diameter of 9.17 mm for Escherichia coli which was moderate.